(1238) Planning strategies for development of new items استراتيجيات التخطيط لتطوير عناصر جديدة - Hamza, Abdel-Kader (The Institute Of National Planning., 2018)
In the following we deal with parallel - Planning strategies for the development of a new item. let us assume that several proposals for developing the new items are available.